Unusual Lifespan of Edwards' Syndrome in COVID-19 Era - Suryaningrat, Filla Reviyani; Hudayari, Devatri; Amalda Ediwan, Natasha; Rita Mardhiya, Wan; Aprilia Kadi, Fiva; Primadi, Aris; Yuniati, Tetty (Faculty of Medicine, Universitas Padjadjaran, 2024)
Edwards' syndrome is caused by an extra chromosome on the 18th chromosome. Patients with this diagnosis have median survival of only 3-14.5 days, with the majority of infants with full trisomy 18 type die before or shortly after they are born. There is only supportive treatment available for Edwards’ syndrome. During the COVID-19 pandemic, providing health services was challenging, leading to less than optimum treatments added by patients’ reluctance to visit healthcare facilities due to the fear of COVID-19 transmission. This case study presented an infant with Edwards’ syndrome with major malformation. The patient had several organ problems, was admitted to the NICU, and continued with home care for monitoring for 6 months. Patient then died at 9 months of age. Maintaining the best quality of life for this patient was very challenging for parents and healthcare providers. Since the management for this type of sydnome is more palliative, good education, information, and psychosocial supports for the parents are needed to prepare them with the worst conditions, which was especially more challenging during the COVID-19 pandemic.